2021
DOI: 10.3346/jkms.2021.36.e6
|View full text |Cite
|
Sign up to set email alerts
|

Process of Obtaining Social Consensus and 3-Year Functional Outcomes of the First Hand Allotransplantation in Korea

Abstract: Background: On February 2, 2017, the surgical team of ten board-certified hand specialists of W Hospital in Korea successfully performed the nation's first hand transplantation at Yeungnam University Medical Center (YUMC). This paper reports on the legal, financial, and cultural hurdles that were overcome to open the way for hand transplantation and its functional outcomes at 36 months after the operation. Methods: W Hospital formed a memorandum of understanding with Daegu city and YUMC to comply with governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In South Korea, despite ethical and legal challenges, the first case of hand transplantation was performed in 2017 [59], followed by a second successful case in 2021 by the Severance Hospital team. However, controversy still exists regarding the practice of such transplantations for non-life-threatening reasons, considering the risk of side effects of lifelong immunosuppressive therapy.…”
Section: Composite Tissue Transplantationmentioning
confidence: 99%
“…In South Korea, despite ethical and legal challenges, the first case of hand transplantation was performed in 2017 [59], followed by a second successful case in 2021 by the Severance Hospital team. However, controversy still exists regarding the practice of such transplantations for non-life-threatening reasons, considering the risk of side effects of lifelong immunosuppressive therapy.…”
Section: Composite Tissue Transplantationmentioning
confidence: 99%
“…The first hand transplantation was unofficially performed in Korea in 2017. 3 This operation achieved good results for the patient, improving public opinion of the procedure, and hand transplantation was finally included in the Organ Act in 2018. 4 With this amendment and the finalization of the Implementing Rules in 2019, hand transplantation was officially covered by the national insurance of Korea since 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Hand procurement and transplantation in this study were performed similarly to many previous experiences. 3 7 18 19 There are varying opinions on the order of hand procurement within the organ procurement process. 42 However, in Korea, the law stipulates that hand procurement can be performed simultaneously with intraperitoneal organ procurement after an intrathoracic organ is procured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Overall, at 1-year follow-up, return of sensation and protective reflex sensation occurred in all grafted hands, which ultimately allowed the recipients to perform most activities of daily life. Woo et al 77 reported on the functional outcome at 36 months after the first hand allotransplantation in Korea in 2017 and showed satisfactory progress in both motor and sensory functions. These results correlated with functional brain magnetic resonance imaging showing significant cortical reorganization of the corticospinal tract, as well as reinnervation of intrinsic muscles.…”
Section: Cost Analysis Associated Complications Functional Outcomementioning
confidence: 99%